Why the French Law Against Food Waste is a Scientific Innovation - Derambarsh , Arash (Bulletin of Yerevan University C: Jurisprudence, 2025)
The objective of this analysis is to highlight the urgency of quickly obtaining a new effective law against food waste. Indeed, the alarming situation with regard to the social and environmental emergency requires a change in the law. Indeed, on the one hand an increase in impoverishment in our country and increasingly long queues at the “soup kitchen” and on the other hand the emergence of worrying global warming, citizens expect effective, innovative and adapted legal tools. Let us recall that the French law of 3rd February 2016 had positive consequences that we will study. However, we must go further with a new bill against food waste in order to adapt the legal framework to the current situation. This is the objective of this legal analysis.